2021
DOI: 10.1039/d1qo00458a
|View full text |Cite
|
Sign up to set email alerts
|

Aziridine used as a vinylidene unit in palladium-catalyzed [2 + 2 + 1] domino annulation

Abstract: A series of chromone fused methylenecyclopentanes are efficiently constructed in moderate to good yields by Pd-catalyzed [2 + 2 + 1] annulation, in which aziridine is used as a vinylidene unit by cleavage of two C–N bonds for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…Based on the aforementioned experimental results as well as our previous works and relevant reports on the palladium-catalyzed reaction involved norbornene, a plausible reaction pathway for the synthesis of polycyclic compound 4a starting from 3-iodochromone ( 1a ), norbornene ( 2a ), and dimethyl squarate ( 3a ) is proposed in Scheme . A palladium­(II) species A is first generated by oxidative addition of Pd(0) generated in situ from Pd­(OPiv) 2 to 1a , followed by migratory insertion of 2a to afford the palladium­(II) intermediate B , which undergoes base promoted intramolecular ortho -C­( sp 2 )–H activation to provide the five membered palladacycle C .…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Based on the aforementioned experimental results as well as our previous works and relevant reports on the palladium-catalyzed reaction involved norbornene, a plausible reaction pathway for the synthesis of polycyclic compound 4a starting from 3-iodochromone ( 1a ), norbornene ( 2a ), and dimethyl squarate ( 3a ) is proposed in Scheme . A palladium­(II) species A is first generated by oxidative addition of Pd(0) generated in situ from Pd­(OPiv) 2 to 1a , followed by migratory insertion of 2a to afford the palladium­(II) intermediate B , which undergoes base promoted intramolecular ortho -C­( sp 2 )–H activation to provide the five membered palladacycle C .…”
mentioning
confidence: 92%
“…In our recent studies, we have shown that the chromonyl-norbornyl-palladacycle ( CNP ) intermediate derived from 3-iodochromone, norbornene, and Pd(0) catalyst was an active Pd­(II) species, which could further react with α-bromoacetophenones, benzyl bromides, cyclopropenones, and aziridines to construct various chromone-containing polycyclic compounds interested in medicinal chemistry . During our ongoing studies on the reactivity of the CNP intermediate, we found that dimethyl squarate could act as an electrophilic alkylating reagent to react with CNP via oxidative addition for the assembly of norbornane-containing chromones, wherein dimethyl squarate was employed as the solid C1 source in the [2 + 2 + 1] domino annulation (Figure B).…”
mentioning
confidence: 99%
“…In our previous investigations, chromonyl-norbornyl-palladacycle (CNP) generated from 3-iodochromone, norbornene(NBE), and a Pd(0) catalyst has been proved to be an active Pd( ii ) species, which could further react with some electrophilic reagents, including α-bromoacetophenones, 6 benzyl bromides, 7 cyclopropenones, 8 aziridines 9 and o -bromobenzoic acids, 10 affording different kinds of chromone-incorporated derivatives via palladium-catalyzed [2 + 3 + 1], [2 + 2 + 1] and [2 + 2 + 2] domino annulations (Scheme 1A). 11…”
mentioning
confidence: 99%
“…Based on our previous work 6–10,12 and related literature 11,16 on the palladium-catalyzed reaction involving palladacycle intermediates, a plausible mechanism is proposed in Scheme 6. Firstly, Pd(0) species were generated in situ from Pd(OAc) 2 .…”
mentioning
confidence: 99%
“…Hence, exploration of a novel strategy toward the syntheses of chromone derivatives, especially the multifunctionalized chromones, is highly desirable. Considering the character of ring-opening of isoflavones to form the phenoxy anion under basic conditions (Figure e) and the unique properties of isocyanides in organic synthesis as well as our continuous interest in the elaboration of chromonyl-norbornyl-palladacycle intermediate for the construction of various chromone derivatives, we wondered if the phenoxy anion intermediate could be engaged in a ring-closure reaction under palladium-catalyzed conditions, delivering the functionalized chromones, rather than undergoing a competitive decarboxylation event, thus generating the undesired ketone byproduct. Herein, we report our most recent endeavor on the molecular rearrangement of 3-halogenochromones based on functional group transformation; this protocol provides a seemingly direct ortho -C–H amination and ipso -formylation of 3-halogenochromones with isocyanides enabled by palladium catalysis under basic conditions (Figure f).…”
mentioning
confidence: 99%